A compilation of intercultural communication competence activities for summer study abroad - Davidson-Mendez, Stephanie (2024)
This material package and thesis contributes an eight-week material package that study abroad administrators and directors can implement in short-term summer study abroad programs. This thesis and material package works to address devel-oping intercultural competencies through activities during short-term study abroad programs. This material package recognizes the complexities of develop-ing intercultural competencies and aims to provide an applicable structured ap-proach that will guide students to reflect on their study abroad experience and as-sist in taking intercultural competencies into consideration, especially in programs where the main focus is language acquisition. Through a constructivist approach, this thesis and material package seeks to shift away from an essentialist paradigm of culture and intercultural learning on study abroad programs. Recognizing that eight weeks is a limited time, and that intercultural communication competence is a lifelong process, and students will not achieve significant intercultural competency during a summer study program. As such, this material package and thesis aims to provide examples and tools for intercultural mediation throughout the various stages of an eight-week study abroad program and encourage study abroad providers and students towards a flexible and fluid understanding of culture, in turn facilitating greater student reflection and meaningful gains during their sojourn abroad.